PENGARUH BRAND AMBASSADOR, BRAND IMAGE DAN TAGLINE TERHADAP BRAND AWARENESS KONSUMEN TOKOPEDIA DI KOTA PANGKALPINANG - Kholifah Kholifah; Afrizal Afrizal; Fithriawan Nugroho (LPPM STIE PERTIBA Pangkalpinang, 2022)
The growth of competition in the world of e-commerce has required companies to design an effective marketing communication strategy in order to increase the company’s brand awareness. One of the marketing communication strategies that can be used to increase brand awareness is by using Brand Ambassador as brand speakers and also by using taglines as a medium for delivering messages about the company. This study aims to determine and examine the extent of the influence of Brand Ambassador and tagline on brand awareness at Tokopedia Indonesia. The study uses a quantitative approach. The sampling technique used is purposive sampling. The sample of this study was 100 respondents with the criteria Tokopedia e-commerce application and people who have seen and know user of the BTS and Blackpink versions of ads and the tagline “Selalu ada, selalu bisa” from Tokopedia and were respondents who were domiciled in the city of Pangkalpinang. The data collection technique of this research is a survey method using a questionnaire instrument. In processing the data, this research uses IBM SPSS 25 software. This study uses multiple regression analysis. This analysis is used to test the relationship between two or more independent variable and the dependent variable. Based on the research results, it is known that each of the Brand Ambassador and tagline variable partially no and significantly affects brand awareness at Tokopedia Indonesia. The simultaneous calculation shows that the Brand Ambassador and tagline simultaneously have a significantly and significantly affect brand awareness at Tokopedia Indonesia. This shows that the Brand Ambassador and tagline used have been able to increase brand awareness on Tokopedia.